Physical Fitness Level and Body Mass Index For Futsal Extracurriculars - Ahmad Mukarrobin; Muslimin Muslimin; Herri Yusfi (Universitas Sriwijaya, 2023)
This research was conducted with the aim of knowing the level of physical fitness and body mass index of the extracurricular futsal extracurricular participants at Raudhatul Qur'an Payaraman Islamic Boarding School. This research is descriptive quantitative, with a survey research method. The population is MTS level futsal extracurricular participants totaling 30 people. The total sampling technique is used for sampling so that the sample is 30 people, the research instrument uses the Physical Fitness Test and Body Mass Index measurement. The physical fitness level of one person in this study was classified as good (3.33%), 19 students (63.33%) sufficient classification, 10 students (33.33%) poor classification. Based on body mass index, 15 students (50%) were included in the thin category, 15 students (50%) were in the normal category. Based on this research, it was found that the general level of physical fitness was in the moderate category and the body mass index was in the normal category. To have the ability to play futsal properly, good physical condition and ideal body mass index are required. It is hoped that this research can be considered by futsal coaches to improve physical fitness and as a concern for maintaining student body mass index so as to prevent nutritional deficiencies or excess nutrition in students.